Asymptotic properties of the norm of the extremum of a sequence of normal random functions - Matsak, I. K. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
Under additional conditions on a bounded normally distributed random function X = X( t), t ∈ T, we establish a relation of the form $$\mathop {\lim }\limits_{n → ∞ } P(b_n (||Z_n || - a_n ) \leqslant x) = \exp ( - e^{ - x} )\forall x \in R^1 $$ where \(Z_n = Z_n (t) = \mathop {\max }\limits_{1 \leqslant k \leqslant n} X_k (t),(X_n )\) are independent copies of \(X,||x(t)|| = \mathop {\sup }\limits_{1 \in T} |x(t)|\) , and (a n) and (b n) are numerical sequences.